Singing sensation - Stilton, Geronimo (New York : Scholastic, 2009)
Geronimo's friend Champ Strongpaws enrolls him as a contestant in "Mouse Island Idol," despite his strenuous objections, but when the CD he makes is pirated, he enlists the aid of his old friend Hercule Poirat.
Keywords: Children's stories; Action and adventure fiction